Voltage‐dependent conformational changes of Kv1.3 channels activate cell proliferation - Cidad, Pilar; Alonso, Esperanza; Arévalo‐Martínez, Marycarmen; Calvo, Enrique; Fuente, Miguel A.; Pérez‐García, M. Teresa; López‐López, José R. (Journal of cellular physiology, 2021)
The voltage‐dependent potassium channel Kv1.3 has been implicated in proliferation in many cell types, based on the observation that Kv1.3 blockers inhibited proliferation. By modulating membrane potential, cell volume, and/or Ca2+ influx, K+ channels can influence cell cycle progression. Also, noncanonical channel functions could contribute to modulate cell proliferation independent of K+ efflux. The specificity of the requirement of Kv1.3 channels for proliferation suggests the involvement of molecule‐specific interactions, but the underlying mechanisms are poorly identified. Heterologous expression of Kv1.3 channels in HEK cells has been shown to increase proliferation independently of K+ fluxes. Likewise, some of the molecular determinants of Kv1.3‐induced proliferation have been located in the C‐terminus region, where individual point mutations of putative phosphorylation sites (Y447A and S459A) abolished Kv1.3‐induced proliferation. Here, we investigated the mechanisms linking Kv1.3 channels to proliferation exploring the correlation between Kv1.3 voltage‐dependent molecular dynamics and cell cycle progression. Using transfected HEK cells, we analyzed both the effect of changes in resting membrane potential on Kv1.3‐induced proliferation and the effect of mutated Kv1.3 channels with altered voltage dependence of gating. We conclude that voltage‐dependent transitions of Kv1.3 channels enable the activation of proliferative pathways. We also found that Kv1.3 associated with IQGAP3, a scaffold protein involved in proliferation, and that membrane depolarization facilitates their interaction. The functional contribution of Kv1.3‐IQGAP3 interplay to cell proliferation was demonstrated both in HEK cells and in vascular smooth muscle cells. Our data indicate that voltage‐dependent conformational changes of Kv1.3 are an essential element in Kv1.3‐induced proliferation. Ion channels have been involved in proliferation in many tissues, but the underlying mechanisms remain unclear. Here, the authors demonstrate a link between Kv1.3 conformational changes and proliferation, and conclude that voltage‐dependent transitions of the channel regulate cell cycle progression.